Essential study skills : - Burns, Tom (Sage Publication Ltd, 2016)
Practical and interactive, this edition features three brand new chapters to arm you with even more essential skills including how to produce a dissertation, planning your career and focussing on building relationships with lecturers and other students to help you get ahead.